2009
DOI: 10.1160/th09-01-0007
|View full text |Cite
|
Sign up to set email alerts
|

Rare genotypes of protein Z gene are a risk factor for premature myocardial infarction but not protein Z plasma level

Abstract: Protein Z (PZ) is the cofactor of PZ dependent inhibitor (ZPI) that inhibits activated coagulation factor X. PZ was expected to play a role in coronary artery disease (CAD) but with inconsistent clinical findings. We therefore evaluated whether PZ plasma level and/or three genetic variants encoding for low PZ plasma level were associated with premature CAD in stable young post-myocardial infarction (MI) patients. PZ plasma level and three polymorphisms A-13G, G-103A and G79A were determined in 176 young stable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Most were conducted in European countries. The vast majority of the studies investigated low protein Z levels in association with an increased risk of thrombosis (5, 7, 8, 1012, 1423, 2532), whereas four studies evaluated the opposite hypothesis, i.e. whether high protein Z levels were associated with an increased risk of thrombotic events (6, 9, 13, 24).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most were conducted in European countries. The vast majority of the studies investigated low protein Z levels in association with an increased risk of thrombosis (5, 7, 8, 1012, 1423, 2532), whereas four studies evaluated the opposite hypothesis, i.e. whether high protein Z levels were associated with an increased risk of thrombotic events (6, 9, 13, 24).…”
Section: Resultsmentioning
confidence: 99%
“…An association between protein Z deficiency and thrombosis has been demonstrated in animal models (33, 34), but human studies have produced conflicting results (532). Indeed, in four of these studies high circulating levels of protein Z were found to be associated with an increased risk of disease (6, 9, 13, 24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation